Learning from IDA Experience : Lessons from IEG Evaluations - Independent Evaluation Group (World Bank, Washington, DC, 2016)
At the United Nations General Assembly in September 2015, world leaders endorsed 17 Sustainable Development Goals (SDGs) as a successor framework to the Millennium Development Goals (MDGs). Placing economic, social, and environmental sustainability at the center of development, the new agenda has the potential for a historic shift in achieving the goal of ending poverty and promoting shared prosperity. Within this changed and changing context, the operations and modus operandi of the International Development Association (IDA) are being examined. As the world’s largest provider of financial resources to the poorest countries, it is expected to deliver greater results in the new development paradigm. In line with the commitment to learning from the past, this synthesis report presents findings from recent evaluations and analysis from the Independent Evaluation Group (IEG). Focusing on the special themes under IDA16 and IDA17, it aims to offer evaluation evidence on what has and has not worked in IDA priority areas in order to support the IDA18 replenishment discussions.